Dealing with the COVID-19 pandemic in orthopaedics: experiences and procedure in Germany. (2020) - Mueller, Michael; Boettner, Friedrich; Karczewski, Daniel; Janz, Viktor; Felix, Stephan; Kramer, Axel; Wassilew, Georgi I
Abstract : Aims: The worldwide COVID-19 pandemic is directly impacting the field of orthopaedic surgery and traumatology with postponed operations, changed status of planned elective surgeries and acute emergencies in patients with unknown infection status. To this point, Germany's COVID-19 infection numbers and death rate have been lower than those of many other nations. Methods: This article summarizes the current regimen used in the field of orthopaedics in Germany during the COVID-19 pandemic. Internal university clinic guidelines, latest research results, expert consensus, and clinical experiences were combined in this article guideline. Results: Every patient, with and without symptoms, should be screened for COVID-19 before hospital admission. Patients should be assigned to three groups (infection status unknown, confirmed, or negative). Patients with unknown infection status should be considered as infectious. Dependent of the infection status and acuity of the symptoms, patients are assigned to a COVID-19-free or affected zone of the hospital. Isolation, hand hygiene, and personal protective equipment is essential. Hospital personnel directly involved in the care of COVID-19 patients should be tested on a weekly basis independently of the presence of clinical symptoms, staff in the COVID-19-free zone on a biweekly basis. Class 1a operation rooms with laminar air flow and negative pressure are preferred for surgery in COVID-19 patients. Electrocautery should only be utilized with a smoke suction system. In cases of unavoidable elective surgery, a self-imposed quarantine of 14 days is recommended prior to hospital admission. Conclusion: During the current COVID-19 pandemic, orthopaedic patients admitted to the hospital should be treated based on an interdisciplinary algorithm, strictly separating infectious and non-infectious cases. Cite this article: Bone Joint Open 2020;1-6:309–315.